Development of a novel and efficient cell culture flocculation process using a stimulus responsive polymer to streamline antibody purification processes. Issue 11 (29th June 2013) - Kang, Yun (Kenneth); Hamzik, James; Felo, Michael; Qi, Bo; Lee, Julia; Ng, Stanley; Liebisch, Gregory; Shanehsaz, Behnam; Singh, Nripen; Persaud, Kris; Ludwig, Dale L.; Balderes, Paul
ABSTRACT Recent advances in mammalian cell culture processes have significantly increased product titers, but have also resulted in substantial increases in cell density and cellular debris as well as process and product related impurities. As such, with improvements in titer, corresponding improvements in downstream processing are essential. In this study we have developed an alternative antibody harvest process that incorporates flocculation using a novel stimulus responsive polymer, benzylated poly(allylamine), followed by depth filtration. As tested on multiple antibodies, this process demonstrates high process yield, improved clearance of cells and cell debris, and efficient reduction of aggregates, host cell proteins (HCP) and DNA. A wide operating window was established for this novel flocculation process through design of experiments condition screening and optimization. Residual levels of impurities in the Protein A eluate were achieved that potentially meet requirements of drug substance and thus alleviate the burden for further impurities removal in subsequent chromatography steps. In addition, efficient clearance of residual polymer was demonstrated using a fluorescence tagged polymer in the presence of a stimulus reagent. The mechanism of HCP and aggregates removal during flocculation was also explored. This novel and efficient process can be easily integrated into current mAb purification platforms, and may overcome downstream processing challenges. Biotechnol. Bioeng. 2013;110: 2928–2937. © 2013 Wiley Periodicals, Inc.